Shaping Behaviors in Virtual Worlds – Gender, Culture, Education. Teacher’s Reflections from Second Life - Topol, Paweł (Wydawnictwo Naukowe UAM, 2015)
The article focuses on the phenomenon of how human behaviors are shaped in the environments of three-dimensional virtual worlds. The so-called serious virtual worlds are taken into consideration. They are sometimes defined in the literature as social environments. The largest ones – like Second Life which has several millions of user accounts – are indeed multi-national and multi-cultural in character. Users, or residents, take part in social, cultural, artistic events or just explore the virtual space for their own reasons. The total area of Second Life is comparable to several Manhattans, so the opportunities to find new interesting spots or to meet new people seem endless. Some key questions covered in the article are: How do people – through their avatars – perform in the three-dimensional virtual world in communicative situations? Do they copy their physical world behaviors onto the virtual? Do they adopt behaviors from other people/avatars, or maybe they reshape their own? The final question is what possible implications for pedagogy and education are –with reference to learning and teaching practice in 3D environments. Examples from author’s experience in virtual worlds will be given.
Keywords: virtual worlds; Second Life; social behavior; performance; education